1987
DOI: 10.3109/00498258709043984
|View full text |Cite
|
Sign up to set email alerts
|

Molecular electrostatic potential energies and methylation of DNA bases: a molecular orbital-generated quantitative structure-activity relationship

Abstract: 1. The results of molecular orbital (MO) calculations, by the MINDO/3 method, on DNA bases, are reported; which point to a radical mechanism of alkylation. 2. Molecular electrostatic potential energy maps indicate propensity for alkylation by N-methyl-N-nitrosourea at key atoms on DNA bases. 3. A correlation between the MO-derived parameters net atomic charges on heteroatoms and superdelocalizability with percentage alkylation by N-methyl-N-nitrosourea is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Molecular electrostatic potentials (MEP) have been shown to correlate with experimentally based quantities such as σ I , σ R , p K a , α, and β (solvatochromic H bond donor and acceptor parameters). Thus, it is probably not surprising that MEP values, often minima or maxima, have been shown to relate to biological properties such as inotropes, the methylation of DNA bases, anti-HIV activity, and several other responses. , Charged partial surface areas have been computed and applied to the prediction of a variety of experimental physicochemical properties, and although they have not been applied extensively to biological properties it has been suggested that they have much potential in this area . Blaney and co-workers have reported a system for the comparison of molecular surface properties and have shown the application of electrostatic potential and shape properties to the study of β-lactam antibiotics and phosphodiesterase inhibitors.…”
Section: Calculated Propertiesmentioning
confidence: 99%
“…Molecular electrostatic potentials (MEP) have been shown to correlate with experimentally based quantities such as σ I , σ R , p K a , α, and β (solvatochromic H bond donor and acceptor parameters). Thus, it is probably not surprising that MEP values, often minima or maxima, have been shown to relate to biological properties such as inotropes, the methylation of DNA bases, anti-HIV activity, and several other responses. , Charged partial surface areas have been computed and applied to the prediction of a variety of experimental physicochemical properties, and although they have not been applied extensively to biological properties it has been suggested that they have much potential in this area . Blaney and co-workers have reported a system for the comparison of molecular surface properties and have shown the application of electrostatic potential and shape properties to the study of β-lactam antibiotics and phosphodiesterase inhibitors.…”
Section: Calculated Propertiesmentioning
confidence: 99%
“…For any nucleophilic substitution reaction near oxygen (closed contour area), an amount of energy equal to the shielded potential energy surface is required; however remaining part of the molecule is suitable for electrophilic substitution reaction. us it can be asserted that MESP values have been shown to be well related to the biological properties [33][34][35].…”
Section: Some Other Modes Of Vibration At Lower Frequencies Amentioning
confidence: 99%
“…For any nucleophilic substitution reaction near oxygen (closed contour area), an amount of energy equal to shielded potential energy surface is required however remaining part of molecule is suitable for electrophilic substitution reaction. Thus it can be asserted that MESP values have been shown to be well related to biological properties [4,16,18].…”
Section: Electronic Propertiesmentioning
confidence: 99%